Why do people with delusions fail to choose more realistic explanations for their experiences? An empirical investigation. - Freeman, D; Garety, P; Fowler, D; Kuipers, E; Bebbington, P; Dunn, G (2004)
Delusions can be viewed as explanations of experiences,. By definition, the experiences are insufficient to merit the delusional explanations. So why have delusions been accepted rather than more realistic explanations? The authors report a study of alternative explanations in 100 individuals with delusions. Patients were assessed on the following criteria: symptom measures, the evidence for the delusions, the availability of alternative explanations, reasoning, and self-esteem. Three quarters of the patients did not report any alternative explanation for the experiences on which the delusions were based. These patients reported significantly more internal anomalous experiences and had a more hasty reasoning style than patients who did have alternative explanations available. Having doubt in a delusion, without an alternative explanation, was associated with lower self-esteem. Clinicians will need to develop plausible and compelling alternative accounts of experience in interventions rather than merely challenge patients' delusional beliefs.